The dance of the oppressed: A pedagogical vision from the redefinition of the female body. (The Voz a Vos Bulletin, 2022)
The present investigation refers to the proposal called the dance of the oppressed, which will address a link between the theater of the oppressed, psycho dance, and symbolic violence with the aim of fracturing the gender canons imposed by the hetero-patriarchal model.
Keywords: dance of the oppressed; psycho dance; hetero-patriarchal; theater of the oppressed